Ambiente para Representação de Múltiplas Visões de Requisitos: O Metamodelo e Uma Linguagem de Transformação - Kirner, Tereza Gonçalves; Prado, Antônio Francisco do; Lima, Maria Adriana Vidigal de; Gratão, Rogéria Cristiane (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de Software, 1996)
This article describes an environment to represent multiple views of software requirements. Two essential components of the environment are discussed, that is, the metamodel and a transformation language. The metamodel is a unique, common representation that supports the integrated use of representation techniques for different methods. The language permits to write the metamodel, aiming to automaticaly generate the system codding in an executable language.